2019
DOI: 10.29408/veles.v3i2.1551
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability Analysis of English National Final Examination for Junior High School

Abstract: The aim of this study is to analyze the validity and reliability of the English National Final Examination for Junior High School academic year 2017-2018. This study took one sample of test package as the tests are similar in terms of the content and differ only in the position of test number. This study was undertaken in one of the private schools in South Jakarta and involved two English subject teachers as validators/validity analysts. The data was analyzed by using a descriptive method. Content validity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
(1 reference statement)
0
7
1
Order By: Relevance
“…Frost (2005) elaborates on various types of testing questions such as: error correction, open-ended questions, true or false, and multiple choice. Among the aforementioned questions commonly used in language testing, multiple-choice appears to be the most utilized testing items inside classrooms (Bachman & Palmer, 1996;Hemmati & Ghaderi, 2014;Jayanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Frost (2005) elaborates on various types of testing questions such as: error correction, open-ended questions, true or false, and multiple choice. Among the aforementioned questions commonly used in language testing, multiple-choice appears to be the most utilized testing items inside classrooms (Bachman & Palmer, 1996;Hemmati & Ghaderi, 2014;Jayanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This research is supported to research that was conducted by Putri (2017), she had already proved that from 50 questions of the test only 10 items are invalid. Then, supported by Jayanti, Husna, and Hidayat (2019), they found that most of the test items of English National Final Examination for Junior High School 2017/2018 matched with competence standard and the English Syllabus and graduation standard. Additionally, Sugianto (2017), he analyzed the validity based on test items, and the validity of the whole test was determined based on the percentage of all valid items.…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies that focused on validity and reliability have been conducted by Mistar, J. (2011), Umam (2011), Sugianto (2011, Akib and Ghafar (2015), Ali and Sultana, (2016), Putri (2017), Jayanti, Husna, andHidayat (2019), andFurwana, (2019). Moreover, Bentri, Hidayati, and Rahmi (2016) conducted a study that only focused on applying the authenticity assessment to English class.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is the multiple-choice (MC) in the reading comprehension tests. According to Hemmati and Ghaderi (2014); Jayanti et al, 2019), MC is the most well-known testing item in the side classroom. The quality of MC is determined by the level of its validity, reliability, and discrimination ability (Jannah et al, 2021;Manalu et al, 2019;Arikunto, 2013).…”
Section: Introductionmentioning
confidence: 99%